International Media Meeting. (Maastricht : Agora Studio / Stichting Agora, 1982)
Bastiaans, Christiaan ; Carey, Tobe J. ; Carrion, Ulises ; Davidovich, Jaime ; Fischer, Herve ; Froese, Dieter ; Gajewski, Henryk ; Gherban, Alexandre ; Hoover, Nan ; Hooykaas, Madelon ; Stansfield, Elsa ; Hopkins, John ; Marroquin, Raul ; Muller, Paul ; Palsson, Thor Elis ; Summers, Rod
International Media Meeting, Maastricht, April 19 - 24, 1982. A Program of discussions, intermedia presentations, closing with a panel discussion.
boek